Exploring the pathways of artificial intelligence in promoting rural education development in China - Jianshuo, Dun; Junjie, Zeng; Ying, Guo (Journal of Islamic, Social, Economics and Development, 2025)
With the rapid advancement of technology, artificial intelligence (AI) has gradually permeated the education sector, injecting new vitality into educational transformation. Particularly in rural education—a vulnerable area—AI applications present unprecedented opportunities for revitalization. This paper systematically analyzes the intrinsic logic and practical pathways through which AI empowers rural education. Research indicates that AI can effectively address structural challenges in rural education through four dimensions: resource equalization, precision teaching, virtualized faculty, and intelligent evaluation. Based on field survey data from 12 provincial-level regions, this study finds that a 10% increase in the coverage of AI education platforms correlates with a 7.3% average improvement in rural students’ academic performance. However, risks such as widening digital divides and the neglect of emotional education in technological applications require vigilance. The paper proposes a "government-enterprise-school-community" quadripartite collaboration mechanism to deepen the integration of AI and rural education.